The formation of civic identity among Russian students is inseparable from a commitment to a healthy lifestyle - Mamedova N.M. ,; Ivleva M.I. ,; Vityaev S.M. ,; Akimova A.O. , (Theory and Practice of Physical Culture, 2025)
Abstract Objective of the study – aims to confirm the importance of a healthy lifestyle as an integral part of civic self-identification and civic ideal in the minds of Russian students. Methods and structure of the study. The study involved students of higher educational institutions in Russia, representing eight federal districts. The sample was formed using a non-random method, namely the "snowball" method (N=945). The confidence interval (margin of error) was ±4.64%. The survey was conducted through a developed questionnaire implemented using Google Forms. The main results of the survey were systematized into four thematic blocks. According to gender and age, the respondents were distributed as follows: 58.9% of the respondents were girls, 41.1% were boys. Results and conclusions. The results of the study provided information about the role of the values of a healthy lifestyle and sports in the worldview of Russian students. It was concluded that the values associated with a healthy lifestyle, health care, physical education and sports occupy an important place in the ideas of Russian students about the ideal citizen. At the same time, a tendency has been identified for young people to postpone the practice of a healthy lifestyle to a later period, after achieving career goals. The authors emphasize the need to actively promote a healthy lifestyle among young people, presenting it as an integral part of civic identity and a component of an ideal citizen, as well as focusing on shaping the image of a citizen as a harmoniously developed and successful personality.